Cardiovascular diseases do not influence the mental health outcome of older men with depression over 6 years - Almeida, O.; Alfonso, Helman; Yeap, B.; Hankey, G.; Flicker, L. (2013)
Background: The concept of 'vascular depression' implies that cardiovascular disease facilitates the onset or persistence of depression in later life, and that the natural course of depression should differ according to whether or not vascular pathology is present. Methods: Population-based cohort of 431 older men were diagnosed with depression (prevalent cases) and followed for up to 6 years. We used the Western Australian Data Linkage System to establish the presence of cardiovascular disease (CVD, documented history of coronary heart disease or stroke) and subsequent persistence or recurrence of depression during follow up (ICD-10 codes). Other measures recorded: age, place of birth, education, social support and disadvantage, smoking history, sensory impairment, medical morbidity burden and use of antidepressants. Results: The age of participants ranged from 69 to 86 years and CVD was present in 212 (49.2%) of them. Depressed men with and without CVD had a similar distribution of demographic, lifestyle, social and clinical factors as men without CVD, but higher medical morbidity. One hundred and twenty six (29.2%) men died and another 43 had a recorded diagnosis of depressive disorder between the baseline assessment and the 31st December 2007. Compared with participants without CVD, the adjusted hazard ratio of recurrent or persistent depression during follow up for participants with CVD was 0.78 (95% confidence interval, 95% CI=0.43-1.42). An additional 30 men were identified with depression during a new clinical assessment in 2008-09. Logistic regression showed that the adjusted odds of depression for men with compared to those without CVD was 0.98 (95% CI=0.61-1.59). Conclusion: Persistence or recurrence of symptoms over 6 years in older men with depression is not influenced by the presence of CVD, which raises doubts about the usefulness and validity of the concept of vascular depression. © 2012 Elsevier B.V.